Left hepatic lobectomy in a long-term biliary atresia survivor - Go Miyano; Takuo Hayashi; Atsushi Arakawa; Geoffrey J Lane; Tadaharu Okazaki; Yoichi Ishizaki; Seiji Kawasaki; Atsuyuki Yamataka (Wolters Kluwer Medknow Publications, 2012)
Surgery was performed on day 43 for biliary atresia. Left lobectomy with preservation of Roux-en-y cholecystojejunostomy was performed for refractory cholangitis after 25 years. Our case is currently awaiting liver transplantation. This is the second report of liver resection in a long-term biliary atresia survivor in the English literature.